2004
DOI: 10.1037/0735-7044.118.5.905
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Healthy Aging on Awareness and Fear Conditioning.

Abstract: Fear conditioning has provided a useful model system for studying associative emotional learning, but the impact of healthy aging has gone relatively unexplored. The present study investigated fear conditioning across the adult life span in humans. A delay discrimination task was employed using visual conditioned stimuli and an auditory unconditioned stimulus. Awareness of the reinforcement contingencies was assessed in a postexperimental interview. Compared with young adult participants, middle-aged and older… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
73
0

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(80 citation statements)
references
References 98 publications
7
73
0
Order By: Relevance
“…Several studies have shown impaired conditioning with increasing age (Bellebaum & Daum, 2004;Knuttinen, Power, Preston, & Disterhoft, 2001;LaBar, Cook, Torpey, & Welsh-Bohmer, 2004;Solomon, Pomerleau, Bennett, James, & Morse, 1989;Woodruff-Pak & Thompson, 1988). In the present study, the age (61 years) of one member of the trace group fell in a range that has previously shown impairment relative to younger subjects (Bellebaum & Daum, 2004;LaBar et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…Several studies have shown impaired conditioning with increasing age (Bellebaum & Daum, 2004;Knuttinen, Power, Preston, & Disterhoft, 2001;LaBar, Cook, Torpey, & Welsh-Bohmer, 2004;Solomon, Pomerleau, Bennett, James, & Morse, 1989;Woodruff-Pak & Thompson, 1988). In the present study, the age (61 years) of one member of the trace group fell in a range that has previously shown impairment relative to younger subjects (Bellebaum & Daum, 2004;LaBar et al, 2004).…”
Section: Discussionmentioning
confidence: 58%
“…Furthermore, exclusion of this data did not alter the statistical results. However, previous findings clearly show that age can have a significant impact on awareness and CR acquisition (Bellebaum & Daum, 2004;Knuttinen et al, 2001;LaBar et al, 2004;Solomon et al, 1989;Woodruff-Pak & Thompson, 1988).…”
Section: Discussionmentioning
confidence: 82%
“…The responses were monitored at 200 Hz and stored offline using AcqKnowledge Software for subsequent analysis (BIOPAC Systems). The physiologic data were time locked to cue-card onset, scored for the amplitude of the first interval response, and square-root transformed to attain normality according to conventional methods, as previously described (LaBar et al 2004). Missing data occurred for five participants, and 12 participants were classified as "nonresponders," meaning that they did not show any measurable SCRs, and were removed from the analyses (LaBar et al 2004).…”
Section: Skin Conductance Responses (Scr)mentioning
confidence: 99%
“…The physiologic data were time locked to cue-card onset, scored for the amplitude of the first interval response, and square-root transformed to attain normality according to conventional methods, as previously described (LaBar et al 2004). Missing data occurred for five participants, and 12 participants were classified as "nonresponders," meaning that they did not show any measurable SCRs, and were removed from the analyses (LaBar et al 2004). The SCR data were scored from the remaining 61 participants (16 controls in the emotional condition, 20 controls in the neutral condition, 14 fearful participants in the emotional condition, and 11 fearful participants in the neutral condition).…”
Section: Skin Conductance Responses (Scr)mentioning
confidence: 99%
“…Contingency awareness also appears to be dependent on the age of the subjects in the experiment (LaBar, Cook, Torpey, & Welsh-Bohmer, 2004;LaBar & Disterhoft, 1998). LaBar and colleagues analyzed fear conditioning using skin conductance and found that younger subjects were more likely to be aware of stimulus contingencies as measured by a postexperimental interview.…”
mentioning
confidence: 99%